Global Bioethics. A look from Evangelii Gaudium - Girotto, Sabina (Medicina e Morale, 2024)
The birth of global bioethics is linked to the figure of U.S. biochemist and oncologist Van Rensselaer Potter, who first adopted the expression in the late 1980s, pointing to the need for a new morality capable of combining attention to human health with ecological science and the broader problems of humanity on a global scale. For a long time, however, this perspective was neglected, and a biomedical approach to bioethics prevailed, on which the traditional understanding of bioethics has been based. Thanks to Dutch physician and ethicist Henk Ten Have, whose volume "Global bioethics: an introduction" was recently translated into Italian, Potter's vision has been recovered. The article aims to examine the framework of global bioethics, illustrating its specificity in light of four principles enunciated by Pope Francis in the apostolic exhortation Evangelii Gaudium, which will be used as interpretative criteria for the discipline under consideration. In addition, the centrality of the principle of vulnerability will be highlighted, with a concluding look at the pandemic event, which more than any other has shown the relevance and necessity of this approach.